Echoes of Wisdom: Unveiling Ecological Education in Oral Literature for an Enriched School Literacy Movement - Enny Hidajati; Urip Sulistiyo; Nazurty Nazurty; Mukhlas Abrar (STAI Hubbulwathan Duri, 2024)
One of the issues that is capturing the world's attention today is environmental issues. Ancient societies had a concern for the environment. Environmental education efforts can be implemented in the School Literacy Movement. To that end, this research will answer the following research questions: 2). How is the natural element in the oral literature of society? 3) How are the efforts to revitalize oral literature and the literacy movement in schools? This study used PRISMA (Preferred Reporting Items for Systematic Review) for the search strategy and the systematic review approach on the selected articles. Relevant literature searches were conducted throughout the Garuda portal. Research results have shown that oral literature plays an important role in society. The important position is because oral literature comes with a variety of functions, namely: (1) As a religious means of a string of prayers and hope to God; (2) As a means of recreation after a long day's work; (3) As a means of education to convey messages of goodness from parents to their children; (4) As a remedy, they mixed spells with plants and other objects; (5) As a means of stimulating the economy in the fields of agriculture, plantations, and the sea; (6). A medium of criticism and advice in the social field of society. Attempts at revitalization have been made in several ways. Among them, collecting old literature in the form of encyclopedia books, anthologies, and textbooks. In addition, it is necessary to make efforts to make oral literature more enjoyable for the younger generation.